1995
DOI: 10.1146/annurev.pa.35.040195.003335
|View full text |Cite
|
Sign up to set email alerts
|

Kinins and Endothelial Control of Vascular Smooth Muscle

Abstract: Plasma and vascular kinins stimulate the production of endothelium-derived nitric oxide, prostacyclin and hyperpolarizing factor (which regulates the function of vascular smooth muscle), and endothelial interactions with blood cells. The role of kinins in vasomotion is determined by the rate of production of the peptides by kininogenases and their degradation by kininases, in particular angiotensin-converting enzyme (ACE). Acute increases in plasma kinin levels during exercise or myocardial ischemia indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(62 citation statements)
references
References 46 publications
5
56
0
Order By: Relevance
“…In a model of sepsis (LPS injection), the initial hypotensive response was severely curtailed in mice lacking the B1 receptor. Kinins have been suggested to be mediators of the vasodilatation observed in septic shock (25)(26)(27), and our results indicate that the B1 receptor is involved in the pathophysiological mechanism. The profound vasodilatation seen after LPS may be elicited by nitric oxide (NO), due to B1 receptors in the vasculature releasing NO via calcium-mediated activation of the endothelial NO synthase (27)(28)(29).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a model of sepsis (LPS injection), the initial hypotensive response was severely curtailed in mice lacking the B1 receptor. Kinins have been suggested to be mediators of the vasodilatation observed in septic shock (25)(26)(27), and our results indicate that the B1 receptor is involved in the pathophysiological mechanism. The profound vasodilatation seen after LPS may be elicited by nitric oxide (NO), due to B1 receptors in the vasculature releasing NO via calcium-mediated activation of the endothelial NO synthase (27)(28)(29).…”
Section: Discussionsupporting
confidence: 59%
“…Kinins have been suggested to be mediators of the vasodilatation observed in septic shock (25)(26)(27), and our results indicate that the B1 receptor is involved in the pathophysiological mechanism. The profound vasodilatation seen after LPS may be elicited by nitric oxide (NO), due to B1 receptors in the vasculature releasing NO via calcium-mediated activation of the endothelial NO synthase (27)(28)(29). Because it has been shown that endothelial cells release NO immediately after administration of LPS (30), endothelial NO synthase activated by kinins via the B1 receptor may cause the early hypotensive response to LPS in intact animals.…”
Section: Discussionsupporting
confidence: 59%
“…We explored next the differential regulation of S1P-mediated responses by comparing directly the signaling pathways elicited by S1P with those activated by bradykinin, a well known activator of eNOS in BAEC (39). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include acetylcholine (produced by endothelial cells; see Physical Signals section of this article), adiponectin (produced by perivascular adipose tissues; see Other Hormones and Circulating Mediators section of this article), angiotensin [1][2][3][4][5][6][7] (formed from angiotensin II by angiotensin-converting enzyme 2), bradykinin (produced by vascular kallikrein), endothelin-1, histamine (produced by mast cells), prostacyclin (produced by endothelial cells), prostaglandin E 2 (produced presumably by endothelial cells), and vascular endothelial growth factor (produced in response to hypoxia). 5,14,15,80 …”
Section: Vascular Signalsmentioning
confidence: 99%